A cross-sectional analysis of the prevalence of tooth agenesis and structural dental anomalies in association with cleft type in non-syndromic oral cleft patients - Dimitrios Konstantonis; Alexandros Alexandropoulos; Nikoleta Konstantoni; Maria Nassika (SpringerOpen, 2017)
Abstract Background The aim of this study was to investigate the prevalence of tooth agenesis, microdontia, and tooth malformation among non-syndromic oral cleft patients and their potential association with cleft type and gender. Methods Intraoral records and radiographs of 154 patients (97 males and 57 females) were examined. The variables assessed were tooth agenesis, microdontia, dental malformations, and cleft types. The statistics included chi-square and Fisher's exact tests as well as logistic regression to assess any mutual effects of gender and cleft type on the dental variables. Results Tooth agenesis occurred in 50% of the sample and microdontia in 18%. Non-statistically significant odds ratios for the association of gender and cleft type with tooth agenesis were obtained. Tooth agenesis was substantially higher at the unilateral right CL + P and the bilateral CL + P in quadrant 1 and at the unilateral left CL + P and bilateral CL + P in quadrant 2. It was also higher, at the isolated cleft palate (CP) in quadrants 3 and 4. These results were attributed to teeth 22 (31.8%) and 12 (21.6%) in the maxilla and to teeth 35 (6.1%) and 45 (5.4%) in the mandible. In unilateral CL + P patients, the cleft quadrant that presented tooth agenesis was associated with the side of the cleft. Conclusions Interdisciplinary treatment of the oral cleft patients should take into consideration the high prevalence of tooth agenesis and their association with the different cleft types. The most frequently affected teeth by cleft are by far the upper lateral incisors. Results indicate that tooth agenesis appears to be a genetically controlled anomaly related to the orofacial cleft development through various genetic links and not caused by the cleft disruptive process.